PENGARUH PENERAPAN E-TICKETING TERHADAP TINGKAT KEPUASAN DAN LOYALITAS PENGGUNA JASA KERETA - Artika Surniandari; Haryani Hasan (Jurnal Ekonomi dan Pembangunan, 2025)
The development of information and communication technology today has been felt by all aspects of the life of modern society is no exception in the field of transportation. The gradual shift and has been felt by train service users today is the implementation of e-ticketing as a system change from the use of the manual ticket to electronic and computerized. The purpose of this study is to see if the use of electronic ticket can affect the loyalty of the train service users, in this case, the current Jabodetabek trains under the name of the commuter line. By using Structural Equation Modeling (SEM) method with AMOS software that can estimate model in structural equation model (SEM). In the use of tickets distinguished into daily tickets and subscriptions, the daily ticket is used within a certain period and requires the user to return the validity period while the subscription card can be used onward and only fill the ticket pulse, with the application of this system can be measured user satisfaction and loyalty who chose to use a subscription ticket even at a more expensive price.